Raising the awareness of privacy on the use of internet technology among adolescents - Abror, Muhammad Yusuf; Pratiwi, Miftha; Yusa, Muchammad Yustian; Musdalifah, Farisha Sestri; Murti, Krisna (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2021)
Sustainable Development Goals (SDGs) is the global agreement agreed by United Nation member countries. The agreement aims to assure fair and equitable development throughout the world. SDGs consist of 17 goals, which one of the goals is about information, communication, and technology (ICT). The principle of SDGs target is to make all countries benefit from the use of ICT including Indonesia. The massive use of ICT in Indonesia, especially within the young generation somehow triggers the possibility of cybercrime. It is necessary to increase awareness of the dangers of cyberspace, specifically regarding the use of personal data. Referring to that, this event conducts a program to increase the understanding and awareness of Junior and Senior High School students to be more careful when using their gadgets such as mobile phones, laptops, and computers, and etc. The method of analysis used in this research is qualitative which is a desk study and quantitative through the questionnaire. The results achieved in this service is the increased awareness of adolescents in Junior and Senior High School about the importance of personal data’s security on the internet so that students can be more aware and selective when accessing various websites.